2001
DOI: 10.1099/0022-1317-50-3-243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human serum DNAases on the ability to detect antibiotic-killed Escherichia coli in blood by PCR

Abstract: PCR has proved superior to conventional blood culture for diagnosing bacteraemia in the presence of antibiotics. Nevertheless, even PCR might yield false-negative results if the template DNA were to be cleaved by serum DNAases after antibiotics had induced bacterial death. To evaluate the cleavage of bacterial template DNA by human serum DNAase I, serum samples inoculated with puri®ed Escherichia coli DNA were incubated with increasing amounts of recombinant human DNAase (rhDNAase) and then examined by a PCR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…8,9 In this study, only 12% of PCRpositive patients remained positive at 12 hours and none after 24 hours of antibiotic drug therapy. [7][8][9] The implication of the present study is that antibiotic drug administration not only rapidly kills bacteria but also enables rapid clearance of bacterial DNA from the bloodstream. Reasons for this may include cleavage by human or bacterial DNases, phagocytosis, or catalysis by antibodies.…”
Section: Commentmentioning
confidence: 49%
See 1 more Smart Citation
“…8,9 In this study, only 12% of PCRpositive patients remained positive at 12 hours and none after 24 hours of antibiotic drug therapy. [7][8][9] The implication of the present study is that antibiotic drug administration not only rapidly kills bacteria but also enables rapid clearance of bacterial DNA from the bloodstream. Reasons for this may include cleavage by human or bacterial DNases, phagocytosis, or catalysis by antibodies.…”
Section: Commentmentioning
confidence: 49%
“…We hypothesize that PCR results may remain positive in septicemic neonates even after antibiotic drug therapy. There are no clinical data on this issue, to our knowledge, but animal data [7][8][9] suggest that a positive PCR result persists after starting antibiotic therapy. If this finding were validated for septicemic neonates, it would allow the diagnosis of sepsis in situations in which neonates receive antibiotic agents without a blood culture being performed.…”
Section: T He Ideal Test For the Di-mentioning
confidence: 97%
“…We have evaluated a novel approach based on quantitative detection of bacterial DNA drawn through the CVC. The advantages of a DNA-based approach are that it can work even when patients have been treated with antibiotics (6) and can be automated. The principle of this approach is that the concentration of bacteria (and therefore bacterial DNA) is high in blood drawn through a colonized CVC.…”
Section: Discussionmentioning
confidence: 99%
“…This false-negative result could be explained using human serum DNases, which are known to degrade bacterial DNA. Heininger et al ( 41 ) reported that PCR-based detection of E. coli in serum was reduced by 10% after antibiotic treatment. Residual bacterial DNA may be detected using the PCR method after antibiotic treatment, even at low levels of bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%